2020
DOI: 10.7592/ejhr2019.7.4.bakar
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate and relevant humour in the university classroom: insights from teachers and students

Abstract: When used for the purpose of teaching and learning, humour must be relevant and appropriate to the context. However, what constitutes appropriate and relevant humour is unclear. Past studies have focussed mostly on classifying appropriate and relevant types of humour. Additionally, students’ and teachers’ perceptions of what constitutes appropriate and relevant humour are likely to differ, meaning that the effectiveness of teachers’ humour use may vary depending on the context. With this in mind, it is importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…To sum up, the instances of humor used in a classroom context "may belong to any of these categories or may even emanate from a careful blending of [them]" (Khan, 2012, p. 46). What matters most is that instructional humor should be appropriate or "positive" (Banas et al, 2010;Kim & Park, 2017;Bakar, 2019). In this study, the participants' choices of Investigating Humor Integration in Tunisian Tertiary English Classes: A Comparative Study of Teachers ' and Learners' Perceptions 129 humor types will enlighten the researcher about the extent to which humor is appropriately employed in Tunisian universities and whether its rewards are explored to the full.…”
Section: Humor Classifiedmentioning
confidence: 93%
See 1 more Smart Citation
“…To sum up, the instances of humor used in a classroom context "may belong to any of these categories or may even emanate from a careful blending of [them]" (Khan, 2012, p. 46). What matters most is that instructional humor should be appropriate or "positive" (Banas et al, 2010;Kim & Park, 2017;Bakar, 2019). In this study, the participants' choices of Investigating Humor Integration in Tunisian Tertiary English Classes: A Comparative Study of Teachers ' and Learners' Perceptions 129 humor types will enlighten the researcher about the extent to which humor is appropriately employed in Tunisian universities and whether its rewards are explored to the full.…”
Section: Humor Classifiedmentioning
confidence: 93%
“…Research specifically done in higher education classrooms adds to these typologies two basic related aspects (Petraki and Nguyen, 2016;Kim and Park, 2017;Bakar, 2019). The first aspect relates to the relevancy of humor to course content and it distinguishes 'related' or 'relevant' humor from 'unrelated' or 'irrelevant' humor (Wanzer et al, 2006;Kim & Park, 2017).…”
Section: Humor Classifiedmentioning
confidence: 99%
“…In an analysis of teachers' and students' perception of appropriate humor, Baker (2019) reported four types of appropriate humor. To his participants, appropriate humor is relevant, happens at a suitable time and in a suitable manner, and improves teachers' credibility.…”
Section: Theoretical Background: Humor In Language Classroommentioning
confidence: 99%
“…Touching the third L2 humor use, relevant/irrelevant types of humor, Nussbaum, Holladay, and Comadena (1987) identified two types of humor in classroom: relevant to course content, and not relevant to course content. According to Baker (2019), relevant humor is "related to daily experiences in life; and irrelevant humor is humor that students do not understand" (p.137). Several studies have confirmed that students perceive humor as relevant if it is related to learning content (e.g., Bieg & Dresel, 2018;Sidelinger, 2014).…”
Section: Theoretical Background: Humor In Language Classroommentioning
confidence: 99%
See 1 more Smart Citation